INTERSTELLAR METEOROIDS WITH ALMOST HYPERBOLIC ORBITS - Markina, A. K.; Skoblikova, L. Ya. (Одеські астрономічні публікації, 2017)
Opportunities for detecting interstellar meteoroids with implicit hyperbolic orbits are explored. It is indicated that the idea of their interstellar origin is based on the distribution of hyperbolic orbits of meteoric particles according to elongation of interstellar radiant from solar apex with a due account of conformity in conditions for their close approach to the Earth.